The Influence of the Occupational of Safety & Health and Work Environment on Work Employees Productivity at Production Division of PT Trimitra Chitrahasta - Selvi Yana; Antoni Ludfi Arifin (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This research was conducted at PT Trimitra Chitrahasta. This study aims to analyze how much influence Occupational Safety & Health and work environment have on work productivity in the production department at PT Trimitra Chitrahasta. The research methodology used is a quantitative method. The sample used in this study consisted of 150 respondents. Data was collected using a questionnaire, where each respondent was given 18 questions. The data was then analyzed using validity test, reliability test and classical assumption test using SPSS version 26 program. The results of this study indicate that: (1)The effect of occupational safety and health on productivity has an interpretation value of 4.29 which means good (2)The influence of the work environment on productivity has an interpretation value of 3.95 which means good (3)The R Square value is 64.6% while 35.4% is influenced by other variables that are not included in this study.